2013
DOI: 10.1371/journal.pone.0059008
|View full text |Cite
|
Sign up to set email alerts
|

Visual Experience Determines the Use of External Reference Frames in Joint Action Control

Abstract: Vision plays a crucial role in human interaction by facilitating the coordination of one's own actions with those of others in space and time. While previous findings have demonstrated that vision determines the default use of reference frames, little is known about the role of visual experience in coding action-space during joint action. Here, we tested if and how visual experience influences the use of reference frames in joint action control. Dyads of congenitally-blind, blindfolded-sighted, and seeing indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Dolk et al concluded that active participation of a co-actor is not necessary for the go-nogo correspondence effect to occur. Rather, any external event that is salient and provides a spatial reference frame relative to which the participant codes her or his own response as left or right is sufficient to elicit a correspondence effect (the referential coding account; see also Dittrich et al, 2012Dittrich et al, , 2013Dolk, Liepelt, Prinz, & Fiehler, 2013b;Guagnano et al, 2010;Liepelt, 2014).…”
Section: Action Co-representation Vs Referential Codingmentioning
confidence: 99%
“…Dolk et al concluded that active participation of a co-actor is not necessary for the go-nogo correspondence effect to occur. Rather, any external event that is salient and provides a spatial reference frame relative to which the participant codes her or his own response as left or right is sufficient to elicit a correspondence effect (the referential coding account; see also Dittrich et al, 2012Dittrich et al, , 2013Dolk, Liepelt, Prinz, & Fiehler, 2013b;Guagnano et al, 2010;Liepelt, 2014).…”
Section: Action Co-representation Vs Referential Codingmentioning
confidence: 99%
“…Therefore, given that there were very few (and perhaps only one) fMRI studies and inspired by some behavioral and ERP studies that successfully induced the joint Simon effect with an unseen co-actor (e.g., Tsai et al, 2008 ; Vlainic et al, 2010 ; Dolk et al, 2013b ), the current experiment aimed to re-investigate the joint Simon effect by using event-related fMRI and adopted a pure belief paradigm as in Tsai et al’s (2008) ERP study, in which the participant performed the joint Simon task with a believed human co-actor or a computer co-actor located outside the scanning room. A solo Go/Nogo task served as a control.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it may rely on the participant's position with reference to the co-actor's position (e.g., the participant's response may be coded as “left” if the co-actor is on the right side of the participant). Alternatively, spatial response coding can be based on the relative positions of the participant's and co-actor's response devices (e.g., regardless of the co-actor's position, the participant's response may be coded as “left” if the participant's response button is on the left with respect to the co-actor's response button), and participants may switch between the two reference frames (Dolk et al, 2013b ; Liepelt et al, 2013 ; see also Milanese et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…A logical implication is that the mere knowledge about the co-actor's task, besides being necessary, should also be sufficient to give rise to the Simon effect. In contrast, the referential coding account states that an alternative action is represented simply by virtue of the fact that the co-actor's response constitutes a salient event, which cannot be ignored by the participant and from which the participant's action has to be discriminated, occurring on the side opposite to the participant's response position (Dolk et al, 2011 , 2013a , b ). As a consequence, the knowledge about the co-actor's task should be neither necessary nor sufficient for the Simon effect to occur.…”
Section: Introductionmentioning
confidence: 99%